INFLUENCE OF ORGANIZATIONAL JUSTICE, LEADERSHIP BEHAVIOR, TRUST EMPLOYEE AND JOB SATISFACTION TO ORGANIZATION COMMITMENT OF PT. BRAM - Prastiyo Diatmono (Business and Entrepreneurial Review, 2017)
Purpose of this research is to know the direct effect of  organizational Justice, leadership behavior, employee trust and job satisfaction on employee’s organizational commitment of PT. BRAM. This research used the quantitative approach with survey method. The samples of this research were 110 empoyees selected randomly. The data were obtained by spreading questionnaire and analyzed with path analysis by supporting descriptive statistics. The results of the research concluded: organizational Justice, leadership behavior, employee trust and job satisfaction had a direct effect on employee’s organizational commitment; organizational Justice,leadership behavior, and trust had a direct effect on employee’s job satisfaction; As implication of this research finding PT BRAMhave to improving employee’s organizational commitment through leadership behavior, trust and job satisfaction.